Topografia das artérias e veias hilares em rins de cão (Canis familiaris, L. 1758) da raça Pequinês - Abdo, Maria das Graças Gomes Sandin; Peduti Neto, José; Souza, Wilson Machado de [UNESP]; Miglino, Maria Angélica (Universidade de São Paulo (USP), Faculdade de Medicina Veterinária e Zootecnia (FMVZ), 2000)
Em 30 pares de rins estudaram-se as artérias e veias, no hilo de cão da raça Pequinês. Os ramos arteriais são contados à direita e à esquerda, entre 6 e 16, e 5 e 13, e as raízes venosas, 1 e 7, e 1 e 10; os vasos arteriais são exclusivamente periféricos 100% e 93,3%, e as raízes venosas centrais; os vasos arteriais são iguais em número, 13,3%, e as raízes venosas, 46,6%; os quadrantes craniais são mais densamente povoados. O teste t de Student não é significante, ao nível de 5%, quanto ao sexo e aos rins (direito e esquerdo). O coeficiente de correlação linear de Pearson é positivo entre o número de artérias e veias, nas fêmeas, para ambos os rins, mas inexistente nas mesmas condições entre os machos.

It was studied the arterial and venous vessels of thirty pairs of kidney hili in the Peckingese breed of dog. The arterial branches are counted at right and left sides, the number varying from 6 and 16, and from 5 and 13 and the venous roots, from 1 and 7, and from 1 and 10; the arterial vessels are the same in number, 13.3% and the venous roots, 46.6%; the cranial quadrants are filled more densely. Student t test did not show a significant result at the level of alpha = 0.05, when sexes (males and females) and the sites (right and left) of the kidneys were compared. For the kidneys of both sides, the Pearson linear correlation coefficient analysis showed a positive result when the number of arteries and veins and female condition were compared. The same result, however, was not observed for the males.
Topography of arteries and veins of hili in kidney Peckingese dog (Canis familiaris, L. 1758)
Keywords: Cão; Rins; Vasos sangüíneos; Dogs; Kidneys; Blood vessels